2014
DOI: 10.4103/0974-8237.147090
|View full text |Cite
|
Sign up to set email alerts
|

Complete absence of the posterior arch of C1: Case report

Abstract: Posterior atlas arch anomalies are relatively common, but have a variety of presentations ranging from partial clefts to complete agenesis of the posterior arch. Partial clefts are prevalent in 4% of patients and are generally asymptomatic. However, complete agenesis of the posterior arch is extremely rare. We report the case of a 46-year-old man who presented with upper cervical spine and occipital pain as well as left sided headaches. Imaging revealed congenital complete absence of the posterior arch of C1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Hypoplasia of the basiocciput and agenesis of the occipital condyles resulted in basilar invagination in our patient. Furthermore, although the Welcher basal angle was slightly greater than normal in this patient, we could not recognize the anthropometric elements of the platybasia, suggesting that basilar invagination and platybasia may be independent [8], [9]. The use of these measurements (lines, distances, and angles) helps the diagnosis of alterations of CVJ.…”
Section: Discussionmentioning
confidence: 64%
“…Hypoplasia of the basiocciput and agenesis of the occipital condyles resulted in basilar invagination in our patient. Furthermore, although the Welcher basal angle was slightly greater than normal in this patient, we could not recognize the anthropometric elements of the platybasia, suggesting that basilar invagination and platybasia may be independent [8], [9]. The use of these measurements (lines, distances, and angles) helps the diagnosis of alterations of CVJ.…”
Section: Discussionmentioning
confidence: 64%
“…Some studies have reported the incidence of cervical vertebra congenital anomalies at about 1 in 40,000 births, with a higher incidence in girls (17). Some studies have reported the prevalence of posterior anomalies in cervical vertebrae of about 0.15% (4,5). Anomalies in the first six cervical vertebrae are more likely to occur than other vertebrae in the whole of the spine (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…These anomalies may range from a minor defect to the absence of posterior arch formation. The prevalence of these types of anomalies is reported about 0.15% (4,5). Although it might be no specific symptoms in these patients, and sometimes they are diagnosed accidentally.…”
Section: Introductionmentioning
confidence: 97%
“…A congenital defect of the posterior arch of the atlas is classified into five severity forms ranging from aplasia (absence of the entire arch including the tubercle) to simple clefts because of the incomplete posterior fusion of the two hemiarches above the midline. Dentists performing CBCT should be familiar with and identify these cervical abnormalities and avoid misdiagnosing them as fractures [ 44 , 45 ]. These anatomical variants of the atlas may cause pain in the cervical and head regions, cerebrovascular accidents and more.…”
Section: Discussionmentioning
confidence: 99%